2020
DOI: 10.1073/pnas.1920988117
|View full text |Cite
|
Sign up to set email alerts
|

Epidemics as an adaptive driving force determining lifespan setpoints

Abstract: Species-specific limits to lifespan (lifespan setpoint) determine the life expectancy of any given organism. Whether limiting lifespan provides an evolutionary benefit or is the result of an inevitable decline in fitness remains controversial. The identification of mutations extending lifespan suggests that aging is under genetic control, but the evolutionary driving forces limiting lifespan have not been defined. By examining the impact of lifespan on pathogen spread in a population, we propose that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 67 publications
(100 reference statements)
1
15
0
Order By: Relevance
“…Presumably, phenoptosis, by reducing the futile food consumption by elderly or stressed worms leads to adaptive benefits for the colony. This concept is also fully consistent with the recently published results of mathematical modeling [8]. The authors demonstrated that in a population of short-lived individuals, the spread of infection is limited, and the pathogen clearance is more efficient than in population in which members live longer.…”
Section: Introductionsupporting
confidence: 89%
“…Presumably, phenoptosis, by reducing the futile food consumption by elderly or stressed worms leads to adaptive benefits for the colony. This concept is also fully consistent with the recently published results of mathematical modeling [8]. The authors demonstrated that in a population of short-lived individuals, the spread of infection is limited, and the pathogen clearance is more efficient than in population in which members live longer.…”
Section: Introductionsupporting
confidence: 89%
“…More generally, species lifespans are likely in uenced by pathogen interactions. Populations of species with short lifespans are able to clear pathogens faster, and being short-lived decreases the probability of crossing the species barrier, which typically requires major adaptations to emerge within the rst infected novel host to mediate e cient transmission (29).…”
Section: Discussionmentioning
confidence: 99%
“…The latter even managed to experimentally test his "virogenetic" theory on rodents during his imprisonment in GULAG [34]. Moreover, the infectious burden is one of the most important factors that determine the species-specific lifespan on the evolutionary scale [35]. From the practical point of view, it is important to note that virus-mediated oncolysis can be considered as a side effect defined by the features of cancer cells, e.g.…”
Section: Diversity Of Viruses As the Basis For The Development Of New Ovsmentioning
confidence: 99%